Guidelines 2021 Changes in Guidelines for First Aid - Fiser, Zoran; Bokan, Dalibor (Journal Resuscitatio Balcanica, 2024)
Guidelines for the implementation of first aid measures are part of the Guidelines 2021 of the European Resuscitation Council from 2015. In 2020, the ILCOR Committee made a scientific consensus for this area, and the European Resuscitation Council in 2021 made new recommendations based on this document and reviewed the existing ones. Recommendations for the application of first aid measures include first aid in emergencies and injuries.Recommendations that include emergencies consider the following content: recovery position, optimal positioning for shock, use of bronchodilators in patients with asthma in first aid, recognition of stroke, use of aspirin for chest pain, giving a second dose of adrenaline in anaphylaxis, first aid for hypoglycemia , oral rehydration, first aid for stress - related dehydration, heat stroke management and application of cooling measures, use of oxygen in providing first aid measures in acute stroke, and first aid for presyncope. First aid for trauma includes the following topics: control of life-threatening bleeding, first aid and treatment of open chest injuries, recognition of concussions, cooling burns, dental avulsion, and first aid for eye injuries due to exposure to chemicals.
Keywords: First Aid; Basic Life Support; Emergency medicine; CPR